Integrating the Holocene tephrostratigraphy for East Asia using a high-resolution cryptotephra study from Lake Suigetsu (SG14 core), central Japan. (1st March 2018) - McLean, Danielle; Albert, Paul G.; Nakagawa, Takeshi; Suzuki, Takehiko; Staff, Richard A.; Yamada, Keitaro; Kitaba, Ikuko; Haraguchi, Tsuyoshi; Kitagawa, Junko; Smith, Victoria C.; ,
Abstract: Tephra (volcanic ash) layers have the potential to synchronise disparate palaeoenvironmental archives on regional to hemispheric scales. Highly productive arc regions, like those in East Asia, offer a considerable number of widespread isochrons, but before records can be confidently correlated using these layers, a refined and integrated framework of these eruptive events is required. Here we present the first high-resolution Holocene cryptotephra study in East Asia, using the Lake Suigetsu sedimentary archive in central Japan. The Holocene tephrostratigraphy has been extended from four to twenty ash layers using cryptotephra extraction techniques, which integrates the deposits from explosive eruptions from North Korea/China, South Korea and along the Japanese arc. This Lake Suigetsu tephrostratigraphy is now the most comprehensive record of East Asian volcanism, and the linchpin site for correlating sequences across this region. Major element glass geochemical compositions are presented for the tephra layers in the sequence, which have been compared to proximal datasets to correlate them to their volcanic source and specific eruptions. This study has significantly extended the ash dispersal of many key Holocene marker layers, and has identified the first distal occurrence of isochrons from Ulleungdo and Changbaishan volcanoes. Utilising the high-precision Lake Suigetsu chronology, we are able to provide constrained eruption ages for the tephra layers, which can be transferred into other site-specific age models containing these markers. This new framework indicates that several isochrons stratigraphically bracket abrupt climate intervals in Japan, and could be used to precisely assess the regional and hemispheric synchronicity of these events. Highlights: First detailed Holocene cryptotephra study in a productive volcanic arc setting. Integrated Holocene tephrostratigraphic record of key East Asian isochrons. Improved chronology of many widespread tephra layers. New constraints on volcanism from back-arc volcanoes (Changbaishan & Ulleungdo). Reveals isochrons than can be used to synchronise to the SG14 record.